An equivalent uniform dose-based class solution for cervical cancer radiotherapy - Shaw, William (University of the Free State, 2014)
Cervix cancer radiotherapy treatment consists of external beam radiotherapy (EBRT) and brachytherapy (BT). Currently there exists no method to combine the dose of both modalities in a single dose value or dose distribution. This study derived a method to use the equivalent uniform dose (EUD) concept as a worst case dose estimate for both modalities, and the combination thereof. The EUD was used as dose evaluation tool in clinical brachytherapy planning of 10 patients that received conservative organ at risk (OAR) toxicity avoidance treatment plans. OAR EUD dose constraints were also derived for brachytherapy treatment planning so as to be equivalent to the Gyn GEC-ESTRO guidelines for cervix cancer brachytherapy based on a population of 20 patients receiving 5 high-dose-rate image guided brachytherapy treatments each. Furthermore, a method to escalate tumour dose without increasing OAR dose was investigated using the EUD as a safeguard against OAR over-dosage and exploiting the effects of fractionation radiobiologically and by organ geometry variations. The EUD was also used as an external beam IMRT evaluation tool to calculate suitable planning target volume (PTV) margin sizes for treatment plan optimization and as a quick cumulative dose computation to enable on-line and off-line image guided adaptive radiotherapy (IGART). This study utilizes the underlying mathematical properties of the EUD to act as a method for determining a worst case dose estimate for tumours and OARs. The method is accurate and reliable and easy to use. OAR dose constraints for brachytherapy treatment planning based on EUD prescription were derived and they compare well with existing Gyn GEC-ESTRO recommended methods and constraints. The safety of the EUD as a worst case dose estimate motivates the use thereof in fractionation compensation based treatment planning that strives to maximize OAR dose to a fixed constraint level and maximize tumour dose at no extra toxicity cost. The EUD derived external beam planning margins also corresponded well with the published margin recipes, but showed that margin recipes potentially overestimate the required margin size and that PTV dose levels could be reasonably lower in some cases compared to the CTV dose level and not lead to tumour under-dosage. The EUD is also an effective 4D dose evaluation and planning tool for IGART and can be used to ensure adequate total dose is delivered in a mobile and deforming tumour without overdosing the OARs. The quick and reliable application of this method is its biggest attribute. The mathematical properties of the EUD open the possibility to determine a worst case estimate of cumulative dose in different treatment modalities and when they are used in combination. The application of this estimate can be extended to safe tumour dose escalation in both image guided adaptive brachytherapy (IGABT) and IGART and their combination.

Onlangse vooruitgang in die behandelings metodes vir servikale kanker het verskeie bekommernisse uitgelig waarvan een die vraag is hoe om die kumulatiewe dosis in die uiters mobiele bekkenorgane en kanker gewas te bereken. Hierdie studie toon hoe 'n ―ergste geval skatting‖ van die totale dosis vir normale weefsel en die gewas kan bereken word sonder die noodsaaklikheid om van vervormings velde en dosis buiging gebruik te maak. Die metode gebruik die ekwivalent uniforme dosis (EUD) konsep en dit beskik oor gunstige wiskundige eienskappe vir hierdie toepassing. Hierdie metode is baie vinnig in die berekening van die kumulatiewe dosis vanaf verskeie behandelings fraksies en vanaf verskillende behandelingsmodaliteite in vervormbare geometrië en is maklik om te implementeer. Hierdie toepassing was gebruik om ‗n konserwatiewe bragiterapie behandelings beplanning protokol by ons sentrum vir behandeling te evalueer en beklemtoon 'n paar beperkinge van hierdie spesifieke behandelings tegniek. EUD-gebaseerde dosis beperkings was ook afgelei sodat beeld gebaseerde bragiterapie (IGBT) uitgevoer kon word met hierdie beperkings aangewend op 'n manier soortgelyk aan die GYN GECESTRO standaard van behandeling. Die EUD metode beskik egter oor die bykomende versekering van veiligheid deur middel van 'n betroubare ―ergste geval‖ dosis beraming. Vir hierdie selfde rede kon 'n dosis eskalasie studie uitgevoer word om plaaslike beheer in die primêre servikale gewas te verbeter met 'n aangepaste beeld begeleidings bragiterapie tegniek. Hierdie studie het getoon dat meer behandelings fraksies, met dieselfde gewas en normale weefsel dosis beperkings, lei tot aansienlik hoër gewas dosisse sonder om normale weefsel dosis te verhoog. Deur verder fraksionerings kompensasie toe te pas kan die gewas dosis selfs verder verhoog word vir sommige pasiënte. Die EUD is bewys as 'n nuttige manier om die vereiste beplannings teiken volume marge grootte mee te evalueer vir eksterne bundel bestraling in die vorm van IMRT, sowel as die uitwerking van opstellings korreksie protokolle vir die bekken area in vergelyking met geen korreksie protokol nie. Gebaseer op die EUD resultate lewer die eNAL opstellings korreksie protokol verseker aansienlik hoër dosisse aan die gewas en laer dosisse aan die normale weefsel in vergelyking met wanneer daar geen poging vir korreksies uitgevoer word nie. Aangesien die serviks gewas uiters beweeglik en onderhewig aan vervorming is deur die loop van bestraling, was die EUD ook ondersoek as 'n kumulatiewe dosis determinant om te help met besluitneming tydens aktiewe en dormante aangepaste beeld begeleide bestraling. In beide die aktiewe en dormante tegnieke kon die beoogde gewas dosis bereik word sonder die oortreding van die normale weefsel dosis beperkings, terwyl erge orgaan beweging en gewas vervorming plaasgevind het tydens die behandelings kursus. Hierdie prosedure kon baie spoedig uitgevoer word deur eenvoudig die gegewe dosis tot op hede op te dateer met die EUD.
Thesis (Ph.D. (Medical Physics))--University of the Free State, 2014
Keywords: IGART; IGABT; Worst Case Scenario; Tumour; Organ at Risk; Treatment Planning; Dose Volume Histogram; Cumulative Dose; Equivalent Uniform Dose; Cancer -- Radiotherapy; Radioisotope brachytherapy; Radiation -- Dosage; Cervix uteri -- Cancer